PERAN ORANG TUA DALAM MEMOTIVASI BELAJAR ANAK DI RUMAH DUSUN TEBING RUBUH KECAMATAN SEBAWI TAHUN 2020 - muhammad dono; Astaman (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2022)
The purpose of this study was to find out: 1) The role of parents in motivating children's learning at the home of Tebing Rubuh Hamlet, Sebawi Sub-district for the 2020 Academic Year. 2) How parents motivate their children's learning at home in Tebing Rubuh Hamlet, Sebawi District for the 2020 Academic Year. 3) Factors supporting and inhibiting the role of parents in motivating children's learning at the home of Tebing Rubuh Hamlet, Sebawi District for the 2020 Academic Year. The research method used in this study is a descriptive method with a qualitative approach. In this study the researchers used interview, observation and documentation data collection techniques, while the sources of data in this study were parents, then the data analysis techniques carried out were: data reduction, data display, data verification, while the technique of checking the validity of the data researchers used 2 techniques, namely: triangulation and member check. The conclusions of this study are: 1) the role of parents in motivating children's learning at home, namely: the importance of the role of fathers and mothers. 2) the way parents motivate children's learning at home, namely: giving verbal rewards, providing opportunities for children to show their skills in public, clarifying learning goals to be achieved, informing the results of work that have been achieved, providing positive examples, creating a positive atmosphere. fun in learning, and arouse children's interest. 3) factors supporting and inhibiting the role of parents in motivating children's student learning. The supporting factors are the physical or spiritual condition of the child being healthy, providing role models, cooperation between teachers and parents, families who care about children's Islamic religious education, the inhibiting factor is the lack of enthusiasm for children in learning at home, facilities and infrastructure are still minimal, Islamic religious education low parents, and lack of support from parents.